2016
DOI: 10.1111/mec.13739
|View full text |Cite
|
Sign up to set email alerts
|

Life in leaf litter: novel insights into community dynamics of bacteria and fungi during litter decomposition

Abstract: Microorganisms play a crucial role in the biological decomposition of plant litter in terrestrial ecosystems. Due to the permanently changing litter quality during decomposition, studies of both fungi and bacteria at a fine taxonomic resolution are required during the whole process. Here we investigated microbial community succession in decomposing leaf litter of temperate beech forest using pyrotag sequencing of the bacterial 16S and the fungal internal transcribed spacer (ITS) rRNA genes. Our results reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
232
4
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 351 publications
(262 citation statements)
references
References 81 publications
23
232
4
3
Order By: Relevance
“…NGS consistently confirmed that Ascomycota have highest relative abundances in the early stages of litter decomposition in temperate forests, and then there is a clear shift from Ascomycota to Basidiomycota in the later stages (Voříšková and Baldrian 2013;Purahong et al 2016). However, the presence/absence data show that Ascomycota (66-82%) are much more frequently detected as compared with Basidiomycota (18-33%) across different sampling times during 473 days .…”
Section: Ngs Challenges the Classical View Of Fungal Succession Durinmentioning
confidence: 74%
“…NGS consistently confirmed that Ascomycota have highest relative abundances in the early stages of litter decomposition in temperate forests, and then there is a clear shift from Ascomycota to Basidiomycota in the later stages (Voříšková and Baldrian 2013;Purahong et al 2016). However, the presence/absence data show that Ascomycota (66-82%) are much more frequently detected as compared with Basidiomycota (18-33%) across different sampling times during 473 days .…”
Section: Ngs Challenges the Classical View Of Fungal Succession Durinmentioning
confidence: 74%
“…In addition, the abundance of Ascomycota was higher in the healthy soils than the bacterial wilt infected soils from 0 d to 60 d, which can enhance soil C cycle and plant nutrient uptake 49, 50 . The abundance of Basidiomycota decreased at 30 d and then increased at 60 d and 90 d in the healthy soils, while it decreased both at 30 and 60 d in the bacterial wilt infected soils.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we used the abundant OTUs (OTUs with > 3 reads) for further statistical analysis. To assess the role of the omitted rare OTUs, a Mantel test based on a Bray–Curtis distance measure with 999 permutations was applied to both the full matrix and the one excluding the rare OTUs (Hammer et al, 2001; Hoppe et al, 2016; Purahong et al, 2016b). The result indicated that the removal of rare OTUs from the WIF communities had no effect on community composition ( R Mantel = 0.999, P = 0.001).…”
Section: Methodsmentioning
confidence: 99%